Appendicitis while on alectinib for non-small cell lung cancer: a tale of two case reports - Wheatley-Price, Paul; Wong, Boaz; Shah, Hely; Sekhon, Harman; Moore, Sara (Frontiers in Oncology, 2024)
IntroductionAberrant expression of anaplastic lymphoma kinase (ALK) is found in 3%–7% of patients with non-small cell lung cancer (NSCLC). Alectinib is a tyrosine kinase inhibitor used as first-line treatment targeting ALK-positive tumors. We herein report two cases of appendicitis highlighting it as a rare, possible adverse event of treatment with alectinib.Case presentationThe first case is a 60-year-old woman with a previous history of stage 1 lobular breast cancer and early-stage lung cancer treated with segmentectomy, subsequently presenting with ALK-positive advanced NSCLC. Treatment with alectinib resulted in partial response, but she developed gastrointestinal symptoms that were assessed with computed tomography (CT) of the abdomen revealing right lower quadrant stranding without appendiceal visualization. Her symptoms continued despite an antibiotic course with re-imaging concerning for acute appendicitis, which was successfully treated with appendectomy and amoxicillin–clavulanic acid. The second case is a previously healthy 58-year-old man with advanced ALK-positive NSCLC who was started on first-line treatment with alectinib and subsequently diagnosed with asymptomatic acute appendicitis on re-staging CT abdomen. Signs on CT resolved with amoxicillin–clavulanic acid. Definitive treatment was conducted with a delayed elective appendectomy. Both patients remained on alectinib over the courses of appendicitis without interruption.ConclusionWhile appendicitis has not been previously described as an adverse effect of alectinib, its incidence in two patients at our center within several months following the administration of alectinib raises its suspicion as a possible adverse effect.